Peran Mediasi Digital Marketing dalam Pengaruh Brand image dan Brand Trust Terhadap Purchase Intention Pusat Oleh-Oleh Gudange Tahu Takwa - Ulfaturrosida, Isma; Mardhiyah, Dien (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of brand image and brand trust on purchase intention, mediated by digital marketing, among consumers of Gudange Tahu Takwa (GTT) Souvenir Center. The main issue addressed is the suboptimal digital marketing strategy, which has impacted customer purchase intention, especially among out-of-town visitors. A quantitative approach using explanatory research methodology was employed. A total of 75 respondents were selected, consisting of active social media users and marketplace platform users. Data analysis was performed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results indicate that brand image and brand trust significantly influence purchase intention, both directly and indirectly through digital marketing. Digital marketing has been proven to play a significant mediating role in strengthening the relationship between brand image and brand trust with purchase intention. The findings highlight the importance of developing an integrated digital marketing strategy to enhance customer loyalty and purchase intention.